Under-Five Mortality in India: A Muddled Trip through Millennium Development Goal - 4 - Paramita Sengupta; Purushottam A Giri; Sadhu C Mohaptra (Archives of Community Medicine and Public Health - Peertechz Publications, 2017)
The Millennium Development Goal-4 (MDG-4) had a target of reducing the under-fi ve mortality rate (U5MR) by two-thirds, between 1990 and 2015. When compared to 1990 levels, 17,000 fewer children died each day in 2015. In 2012, UNICEF found that, globally, children born in the poorest 20% of households had only half the chance of surviving to their fi fth birthday as children born in the richest 20% of households. Many countries, including India could not attain the MDG-4. The Sustainable Development Goals (SDGs) seeks to build on the Millennium Development Goals (MDGs) and "complete what these did not achieve, "particularly in reaching the most vulnerable. The SDGs are committed to the full realization of all the MDGs, including the off-track MDGs, by providing focused and scaled-up assistance to least developed countries and other countries in special situations, in line with relevant support programs. MDG-4 failed to achieve its single target of reducing child mortality. This review attempts to provide an insight into the under-fi ve mortality in India. Various internet based popular search engines were used to explore data from literature, which includes PubMed, PubMed Central, Google Scholar, Medknow, and Science Direct. Search was made using the key-word combinations "under fi ve mortality" and "millennium development goals" were used. The search was limited to reviews; meta-analyses and assorted reports were retrieved and evaluated. A total of 25 publications were evaluated for this review article.